A Review of Renewable Technology Integration in Historical Buildings (International Journal of Innovative Research in Computer Science & Technology, 2021)
In recent years, decommissioned historic  structures have been repurposed for private or public use.  Sector consumes over a third of global final energy and  create a large amount of CO2. The need to comply with  energy conservation rules in both new and existing  buildings has encouraged planning and engineering  practices aimed at reducing carbon dioxide emissions  while simultaneously improving interior comfort as well  as functionality. In this article, a devoted scientific effort  must be expended when dealing with historical structures  that require to maintain their essential testimony  knowledge into society. As a result, customized retrofit  methods have been explored and executed without  jeopardizing the architectural integrity of the buildings,  particularly where new uses are anticipated. This research  classifies the utilization of energy efficiency technologies  as well as the deployment of renewable energies in  historic buildings, including such solar and geothermal  energies, and heat pumps as well as other high-efficiency  heating, ventilation, and air conditioning units.
Keywords: Geothermal Energy; Heritage Buildings; Historical Buildings; Renewable Energies; Solar Energy